Innovation Driven and International Cooperation Strategies of High-Tech Enterprises in the Era of Globalization - Ning, Yanbo (Transactions on Economics, Business and Management Research, 2024)
High-tech businesses are under increasing pressure to develop and collaborate globally in order to remain competitive in an era characterized by rapid globalization. This study looks at tactics that are driven by innovation and how important it is for high-tech companies to collaborate internationally. The study looks at how innovation functions as a primary competitive strategy and how international cooperation improves innovation capabilities and market competitiveness. It does this by using case studies and in-depth literature reviews. In particular, the example of Huawei Technologies shows how R&D investment and strategic international relationships support innovation. According to the results, strong international cooperation can greatly improve high-tech businesses' innovation output and market placement. It can also offer important insights into how to overcome common challenges in global market contexts.